Synthesis of new epoxy glucose derivatives as a non-toxic corrosion inhibitors for carbon steel in molar HCl: Experimental, DFT and MD simulation - Rbaa M.; Benhiba F.; Dohare P.; Lakhrissi L.; Touir R.; Lakhrissi B.; Zarrouk A.; Lakhrissi Y. (My University, 2025)
The purpose of this study was to examine the effect of inhibiting corrosion of two biodegradable newly synthesized compound derivatives of D-glucose for carbon steel in 1 M HCl. These compounds were characterized by infrared (IR), Nuclear magnetic resonance (1H and 13C NMR) and Elementary analysis (EA) spectroscopy. The evaluation of the corrosion inhibiting effect was studied using Usual electrochemical methods, DFT calculations and MD simulations. The morphology of the metal surface was characterized by SEM/EDS. However, the gravimetric solutions were analyzed by ICP-OPS and UV-visible spectrometry. This study has shown that these compounds provide good protection for carbon steel against corrosion inhibition in the 1 M HCl. Analyzes by scanning electron spectroscopy coupled with energy dispersion spectroscopy (SEM/EDS) show that the two inhibitors have been well adsorbed on the metal surface. The theoritical studies are in good agreement with those obtained from Electrochemical methods. © 2020 Elsevier B.V.